2018
DOI: 10.1017/jwe.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Entrepreneurship in Emerging Wine Regions

Abstract: This study investigates a hypothesized positive relationship between the number and strength of network ties and the performance of wineries in emerging production regions, which may face different challenges than wineries found in well-established regions. Results corroborate expectations that greater ties to competitors and firms in related tourism food and lodging sectors bolster performance. (JEL Classification: Q130)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(15 reference statements)
0
11
0
1
Order By: Relevance
“…For example, both Grängsjö and Gummesson [47], and Wang and Xiang [48] examined cooperative efforts and marketing alliances of tourism businesses through reciprocal exchange of resources. Others found that trust and social network ties were important to both prospective and current tourism and related business owners in terms of starting and operating their businesses [12,25,49]. Some studies also investigated from the tourists' perspective [27] suggesting that tourism creates and strengthens social ties between families and friends [50] and fosters interactions with others [51].…”
Section: Social Capital In Tourism Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both Grängsjö and Gummesson [47], and Wang and Xiang [48] examined cooperative efforts and marketing alliances of tourism businesses through reciprocal exchange of resources. Others found that trust and social network ties were important to both prospective and current tourism and related business owners in terms of starting and operating their businesses [12,25,49]. Some studies also investigated from the tourists' perspective [27] suggesting that tourism creates and strengthens social ties between families and friends [50] and fosters interactions with others [51].…”
Section: Social Capital In Tourism Studiesmentioning
confidence: 99%
“…Hall [52] highlighted that networks and social capital were critical to the success of food and wine tourism development in rural New Zealand. Franken et al [12] identified the importance of social capital in supporting wine entrepreneurs establishing operations in new regions in the U.S. Although some researchers have examined wine tourism regional development focusing on winery businesses' competition and competitive behaviors [52,53], this literature review yields no information on the level of community social capital associated with wine trails.…”
Section: Social Capital In Tourism Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While California remains the uncontested leader, with 86% of production by volume (Wines Vines Analytics, 2019), virtually all continental U.S. states have established local wine industries. The essential pull factor behind the expansion of wine-making into nontraditional regions has been consumer demand for agritourism experiences (Franken, Gómez, and Ross, 2018), with 30 million annual wineries visits supporting a labor force of more than 50,000 (WineAmerica.Org., 2014). Government policies leveraging wine production to support rural economies have also played a fundamental role (Clark and Jablonski, 2018), with three major thrusts: (1) a legislative shift towards a simpler regulatory and fiscal environment for alcohol production (Lee and Gartner, 2015); (2) an extensive effort to both develop grape varieties better suited to suboptimal growing conditions and improve quality (e.g., the Northern Grape Project 1 for cold climates, see Lee and Gartner (2015)); and (3) state branding and marketing campaigns supporting local agricultural products (Nganje, Hughner, and Lee, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Economic results have established the positive effect of synergy and coherence of wine route stakeholders’ action (Brunori and Rossi, 2000). When a wine route is successful, its economic impact on the vineyard is twofold: an increase in the profitability of existing activities and the discovery of new entrepreneurial opportunities in emerging wine regions (Franken, Gómez, and Ross, 2018). Thus, the greater the number of visitors, the greater the demand for wine and complementary products and services on the property.…”
Section: Introductionmentioning
confidence: 99%